Downstream consequences of disclosing defaults: influences on perceptions of choice architects and subsequent behavior. Issue 1 (2nd September 2021) - Michaelsen, Patrik; Nyström, Lina; Luke, Timothy J.; Hedesström, Martin
ABSTRACT: Transparency is a key factor in determining the permissibility of behavior change interventions. Nudges are at times considered manipulative from failing this condition. Ethicists suggest that making nudges transparent by disclosing them to decision makers is a way to mitigate the manipulation objection, but questions remain as to what downstream consequences disclosing decision makers of a nudge may cause. In this registered report, we investigated two such consequences: (1) whether disclosure affects perceptions of the choice architect and (2) whether disclosure influences subsequent behavior. To these ends, we present data from three pilot studies and two main experiments (total N = 2177). In both experiments, we used defaults to nudge participants towards prosocial behaviors with real consequences. Experiment 1 employed a mixed design examining changes in perceptions of the choice architect for participants presented with a nudge disclosure before or after choosing. Experiment 2 extended by investigating the effects of disclosure on the default effect, perceptions of the choice architect, and on a subsequent prosocial choice task. Results showed that (1) when presented before choosing the nudge disclosure did not influence perceptions of the choice architect. However, when presented after, perceptions deteriorated. (2) The disclosure, regardless of when presented, had no effect on participants' behavior in a subsequent non-nudged choice. Additionally, the disclosure did not affect the nudge's influence on the initial choice. We conclude that lack of transparency can hurt choice architects' reputation and discuss under what circumstances this may materialize behaviorally. Materials, data, and code are available at osf.io/463af/.